Analysing collaborative demand and supply networks of SMEs. (20th April 2006) - Antonelli, Dario; Cassarino, Irene; Villa, Agostino
A widely accepted commonplace states that collaborative behaviours among the economic actors in a region could assure an increased efficiency and effectiveness to the whole social-economic context. When addressing clusters of Small-Medium Enterprises (SMEs), the aim is to promote collaborative actions, starting from co-design to co-operative supply chain management. The difficulties arise from the scarce comprehension of the process organisation inside industrial bodies and the difficult assessment of the overall cluster efficiency, effectiveness and economic convenience. This paper analyses different meanings and possibilities of collaboration among SMEs with the goal of introducing a 'management control panel' for collaborative networks.